UKURAN PERUSAHAAN MEMODERASI HUBUNGAN LEVERAGE TERHADAP RETURN SAHAM - Agus Wahyudi (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2026)
This research aims to examine the effect of leverage on stock returns and test whether company size is able to moderate the effect of leverage on stock returns in State-Owned Enterprise companies listed on the Indonesia Stock Exchange in 2018-2020. This research is quantitative descriptive research using an associative approach. The population in this study was 22 companies. The sampling technique uses purposive sampling, the total sample is 16 companies so the total observations are 48. The research results show that leverage has no effect on stock returns. Then, company size is unable to moderate the influence of leverage on stock returns in State-Owned Enterprises listed on the Indonesia Stock Exchange in 2018-2020. As much as 22.6% of the stock return variable can be explained by the leverage variable and company size as moderating the relationship between leverage and stock returns.